2013
DOI: 10.5966/sctm.2013-0100
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Multipotent Adult Progenitor Cell Therapy Attenuates Activated Microglial/Macrophage Response and Improves Spatial Learning After Traumatic Brain Injury

Abstract: We previously demonstrated that the intravenous delivery of multipotent adult progenitor cells (MAPCs) after traumatic brain injury (TBI) in rodents provides neuroprotection by preserving the blood-brain barrier and systemically attenuating inflammation in the acute time frame following cell treatment; however, the long-term behavioral and anti-inflammatory effects of MAPC administration after TBI have yet to be explored. We hypothesized that the intravenous injection of MAPCs after TBI attenuates the inflamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
73
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 66 publications
(80 citation statements)
references
References 41 publications
4
73
0
2
Order By: Relevance
“…Thirty-eight studies met inclusion criteria and underwent data extraction and quality assessment. Of these studies, some reported more than one pertinent outcome measure so that a total of 10 studies presented data for RR outcomes (1625), 14 presented data on LV outcomes (23, 2638), 21 assessed NSS outcomes (1721, 2326, 28, 29, 31, 36, 3853), and 13 presented data on MWM testing (17, 18, 24, 26, 28, 29, 36, 38, 4953). Specific study characteristics are listed in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Thirty-eight studies met inclusion criteria and underwent data extraction and quality assessment. Of these studies, some reported more than one pertinent outcome measure so that a total of 10 studies presented data for RR outcomes (1625), 14 presented data on LV outcomes (23, 2638), 21 assessed NSS outcomes (1721, 2326, 28, 29, 31, 36, 3853), and 13 presented data on MWM testing (17, 18, 24, 26, 28, 29, 36, 38, 4953). Specific study characteristics are listed in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…A decrease in body temperature, known to decrease inflammatory responses, resulted in an increase in cellular proliferation frequency of dentate gyrus DCX‐immunoreactive cells 7 days post‐trauma [67]. Given the immunomodulatory potential of MSC in TBI [26, 33], it is conceivable that the anti‐inflammatory effects of MSCs contribute to neurogenesis in our model.…”
Section: Discussionmentioning
confidence: 99%
“…Stimulation of the thalamic region years after TBI improves arousal level, motor control, and behavioral responses [81], supporting preservation of the thalamus as a new and promising target to improve TBI outcome. Lastly, the reduction in neuroinflammatory responses holds promise in other neurodegenerative diseases besides TBI [26, 33, 37], such as Alzheimer's disease [82] and multiple sclerosis [83].…”
Section: Discussionmentioning
confidence: 99%
“…Pati and colleagues have shown that MSCs prevent Evans blue dye extravasation (preserved BBB) after TBI and that this effect is due to up regulation and organization of the tight junctional proteins, VE‐cadherin and β‐catenin. These data have been replicated using different cell types (MAPC and bone marrow mononuclear cells [BMMNCs]) using similar TBI models and various methods to evaluate permeability . The reproducibility in multiple laboratories with various cell types and injuries support that this is one of the principal beneficial mechanisms of action with these cell types.…”
Section: Edema and Icp: Is It A Valid Endpoint?mentioning
confidence: 84%